PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 61 HARAPAN BARU KECAMATAN MANDAU KABUPATEN BENGKALIS - Siagian, Juliani; Lazim N, Lazim N; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted because of the low learning outcomes for social studies at New Hope Elementary School 61 with the number of students 20 people, consisting of 10 male students and 10 female students. Shown that learners have not been able to reach minimum completeness criteria (KKM) established by the 70 schools in the second semester of the school year 2015/2016 has been specified in the curriculum. Meanwhile, the number of students who reached KKM 9 students (45.00%) while those not reached KKM 11 students (55.00%). The purpose of this research to improve learning outcomes IPS to see the activity of teachers at the first meeting of the first cycle is the number of scores obtained in the first meeting of the cycle I was 12 with a percentage of 50.00% with less category, while in the second meeting of the first cycle of teacher activity score increased be 58.33% with enough category. In the first cycle of teacher activity II total score was 79.17% with a good category and at the second meeting of the second cycle the number of teachers activity score is 91.60% with very good category. Additionally the activity of the students at the first meeting of the first cycle was 41.67% with less category, while in the second meeting of the first cycle of the total score is 54.17% with the category enough. At the first meeting of the second cycle is the number of scores obtained 70.83% in both categories, while in the second meeting of the second cycle of the score obtained is 87.50% with very good category. In addition to the increase of the activities of teachers and students, improving student learning outcomes from basic score to UH I averaging 66.50 into 69.50 with an increase of 4.51% to UH II which increased to 81.25 with the percentage increase of 22, 18%.Key Words: Make a Match, learning outcomes IPS